Рассказы и сказки - Ушинский Константин Дмитриевич (Школьная библиотека, 2004)
Экземпляры: ДБ (20210927) / Инвентарный номер: 54320 / Цена: 120.00 / Сис.шифр: 84(2Рос=Рус)1 / Авт.знак: У 94 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)1-4